Sphingolipids metabolism alteration in the central nervous system: Amyotrophic lateral sclerosis (ALS) and other neurodegenerative diseases. (April 2021) - Bouscary, Alexandra; Quessada, Cyril; René, Frédérique; Spedding, Michael; Turner, Bradley J.; Henriques, Alexandre; Ngo, Shyuan T.; Loeffler, Jean-Philippe
Abstract: Sphingolipids are complex lipids. They play a structural role in neurons, but are also involved in regulating cellular communication, and neuronal differentiation and maturation. There is increasing evidence to suggest that dysregulated metabolism of sphingolipids is linked to neurodegenerative processes in amyotrophic lateral sclerosis (ALS), Parkinson's disease and Gaucher's disease. In this review, we provide an overview of the role of sphingolipids in the development and maintenance of the nervous system. We describe the implications of altered metabolism of sphingolipids in the pathophysiology of certain neurodegenerative diseases, with a primary focus on ALS. Finally, we provide an update of potential treatments that could be used to target the metabolism of sphingolipids in neurodegenerative diseases.